The seventeen second miracle - Wright, Jason F. (New York : Berkley Books, 2010)
Cole Connor has become a patient teacher, and now he has invited three struggling teenagers to visit him on his front porch to learn about Rex Connor--and the Seventeen Second Miracle. Together they will learn how Rex Connor could have allowed seventeen seconds to destroy him, but instead he chose to live every day believing the smallest of acts could change the world for good.
Keywords: Fathers and sons -- Fiction; Teachers -- Fiction; High school students -- Fiction; Life change events -- Fiction; Charlottesville (Va.) -- Fiction; American fiction -- 21 century